Measuring how communication and engagement efforts help deliver outcomes - Schuetz, Tonya; Meadu, Vanessa; Atakos, Vivian; White, Julianna M.; Schubert, Cecilia; Urrea Benítez, José Luis; Ampaire, Edidah L.; Radeny, Maren A.O.; Mungai, Catherine; Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Key messages  Initial steps towards outcome-focused monitoring, evaluation & learning (MEL) on communication and engagement can be small, but they must be systematic.  To achieve broad participation, MEL needs to be lean and do-able.  Well-designed MEL adds value by feeding information and lessons into future work and decision-making.  Adequate time must be devoted to embedding MEL into the initial activity plan and following it throughout the communication engagement activity and afterwards.  MEL is easier when it is done more often. It is helpful to draw upon resource persons.  Preparatory work and capturing feedback through mechanisms built into the communication- engagement activity is more informative than soliciting responses afterwards.  Peer exchanges about MEL practices and adaptable templates are beneficial.  Aligning specific communication activities with the established impact pathway can ensure more strategic and focused activities and products that contribute to outcomes and impact.